2021
DOI: 10.1080/13670050.2021.2003293
|View full text |Cite
|
Sign up to set email alerts
|

The extent and predictors of linguistically responsive teaching in Southwest China

Abstract: The study of multilingualism has gained prominence due to increases in linguistically diverse student populations. This paper aims to contribute to research on multilingualism by addressing schoolteachers' beliefs and practices related to linguistic diversity. A unique sample of 606 teachers across ten minority-dominant schools from Southwest China participated in the survey study. The results show that schoolteachers hold both monolingual and multilingual beliefs. Teachers' beliefs are mainly positive about m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Some studies have shown that ethnic minority teachers outperform their ethnic majority colleagues and contribute to the positive learning outcomes of ethnic minority students Kleen et al, 2019). However, an earlier survey study undertaken by us (Liu et al, 2021) suggests that someone's ethnic minority status does not necessarily mean an exemption from in-group stereotypes. As such, the research field requires hearing more voices from ethnic minority teachers regarding their students and teaching to increase educational equity.…”
Section: What Are the Main Insights That The Paper Provides?mentioning
confidence: 92%
See 1 more Smart Citation
“…Some studies have shown that ethnic minority teachers outperform their ethnic majority colleagues and contribute to the positive learning outcomes of ethnic minority students Kleen et al, 2019). However, an earlier survey study undertaken by us (Liu et al, 2021) suggests that someone's ethnic minority status does not necessarily mean an exemption from in-group stereotypes. As such, the research field requires hearing more voices from ethnic minority teachers regarding their students and teaching to increase educational equity.…”
Section: What Are the Main Insights That The Paper Provides?mentioning
confidence: 92%
“…In particular, deficit thinking in education remains a severe barrier to creating a caring classroom climate and engaging in culturally responsive teaching (Walker, 2011;Wang, 2022). For example, researchers (Liu et al, 2021;Yuan, 2018;Zhang & Wang, 2016) suggest that Han ethnic majority teachers in China exhibited unclear attitudes towards ethnic diversity, often considering minority cultures as inferior to the dominant Han culture. The results of these studies show that these teachers felt they lacked sufficient academic and cultural readiness to teach a diverse student population.…”
Section: What Are the Main Insights That The Paper Provides?mentioning
confidence: 99%
“…In other words, Yosso conceptualizes different forms of capital based on Bourdieu's theorization of cultural and social capital, while offering a critique of how these notions have been used by others to construct racialized communities as culturally deprived and White middle-class culture as the norm. This means that marginalized youth are often expected to disassociate from their cultures and adapt to inherently unjust educational structures where their cultural identities and knowledge (e.g., home languages) are either overlooked or rejected (Agirdag, 2010;Çolak, 2020;Liu et al, 2022).…”
Section: Ccwmentioning
confidence: 99%
“…Ethnic minority groups in Chinese context usually refer to indigenous minorities who have historical settlements in China (Liu et al, 2021). Prior research contextualized in China has revealed that the experiences, histories, and values of ethnic minority people are highly underrepresented in educational contexts (Chu, 2015;Harrell & Ayi, 1998;Xiang & Yenika-Agbaw, 2019;Zhao & Postiglione, 2010).…”
Section: Representation Of Ethnic Minority Groups In Chinese School T...mentioning
confidence: 99%